2012
DOI: 10.1016/j.thromres.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of PAI-1 and platelet GP Ia may associate with impairment of renal function and thrombocytopenia in Puumala hantavirus infection

Abstract: Introduction Puumala virus (PUUV) infection is a viral hemorrhagic fever with renal syndrome (HFRS) characterized by thrombocytopenia and acute impairment of renal function. We aimed to assess whether genetic polymorphisms of platelet antigens together with those of von Willebrand factor (VWF) and plasminogen activator inhibitor (PAI-1) correlate with disease severity. Patients and methods 172 consecutive hospital-treated patients with serologically confirmed acute PUUV infection were included. Platelet glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
1
35
0
3
Order By: Relevance
“…In patients with HFRS caused by the more severe Asian prototype hantavirus species, Hantaan virus, trombocytopenia has also predicted severe AKI [51]. On the other hand, PUUV-infected carriers of plasminogen activator inhibitor-1 G-allele have more severe AKI and coincidently less severe thrombocytopenia [19]. Thus, the association between renal impairment and thrombocytopenia in hantavirus infections remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with HFRS caused by the more severe Asian prototype hantavirus species, Hantaan virus, trombocytopenia has also predicted severe AKI [51]. On the other hand, PUUV-infected carriers of plasminogen activator inhibitor-1 G-allele have more severe AKI and coincidently less severe thrombocytopenia [19]. Thus, the association between renal impairment and thrombocytopenia in hantavirus infections remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort consisted of 556 PUUV-infected patients, who had participated in our previous clinical studies [12,17,18,19,24,25,26,27,28,29,30,31,32,33,34,37,38,39,40,41]. The diagnosis of acute PUUV infection was serologically confirmed in all cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients also participated in our previous studies [17,22,[24][25][26][27][28][29][30][31][32][33] . All patients were examined during the acute phase of the disease, and the diagnosis of acute PUUV infection was serologically confirmed [34][35][36][37] .…”
Section: Methodsmentioning
confidence: 99%
“…Hantavirus fever caused by PUUV can differ in disease severity from mild-form NE to severe kidney injury and some fatal rare cases [29], and the host influences the clinical picture [10,30,31,32]. Recently, Tervo et al [26 ]demonstrated that smoking is a risk factor associated with severity of AKI in patients with acute PUUV infection.…”
Section: Discussionmentioning
confidence: 99%